Can we HALT obesity following lung transplant? A Dietitian‐ and Physiotherapy‐directed pilot intervention. Issue 8 (21st July 2022) - Emsley, Christie; Snell, Greg; Paul, Eldho; Fuller, Louise; Paraskeva, Miranda; Nyulasi, Ibolya; King, Susannah
Abstract: Introduction: Unintentional weight gain, overweight and obesity following solid organ transplantation (SOT) are well‐established and linked to morbidity and mortality risk factors. No interventional studies aimed at prevention have been undertaken among lung transplant (LTx) recipients. The combination of group education and telephone coaching is effective in the general population but is untested among SOT cohorts. Methods: A non‐randomized, interventional pilot study was conducted among new LTx recipients. The control group received standard care. In addition to standard care, the intervention involved four group education and four individual, telephone coaching sessions over 12‐months. Data collection occurred at 2 weeks, 3‐ and 12 months post‐LTx. Measurements included weight, BMI, fat mass (FM), fat mass index (FMI), fat‐free mass (FFM), fat‐free mass index (FFMI), waist circumference (WC), visceral adipose tissue (VAT), nutrition knowledge, diet, physical activity, lipid profile, HbA1C, FEV1, six‐minute walk distance and patient satisfaction. Results: Fifteen LTx recipients were recruited into each group. One control participant died 120 days post‐LTx, unrelated to the study. There were trends towards lower increases in weight (6.7±7.2 kg vs. 9.8±11.3 kg), BMI (9.6% of baseline vs. 13%), FM (19.7% vs. 40%), FMI, VAT (7.1% vs. 30.8%) and WC (5.5% vs. 9.5%), and greater increases in FFM and FFMI (all P > .05), among the intervention group by 12 months. The intervention was well‐accepted by participants. Conclusion: This feasible intervention demonstrated non‐significant, but clinically meaningful, favorable weight and body composition trends among LTx recipients over 12 months compared to standard care.